2018
DOI: 10.1016/j.cpc.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations in hybrid particle-continuum schemes: Pitfalls and caveats

Abstract: Heterogeneous multiscale methods (HMM) combine molecular accuracy of particle-based simulations with the computational efficiency of continuum descriptions to model flow in soft matter liquids. In these schemes, molecular simulations typically pose a computational bottleneck, which we investigate in detail in this study. We find that it is preferable to simulate many small systems as opposed to a few large systems, and that a choice of a simple isokinetic thermostat is typically sufficient while thermostats su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In the model we studied, the fluid is Newtonian for small packing fractions, but develops a yield stress as the packing fraction increases, similar to several previous works [65,[69][70][71][72], as seen in Figure 2a-c. One can see the rise of solid-like properties in those fluidic systems.…”
Section: Shear Thickening Due To Functional Particle Infusionsupporting
confidence: 80%
“…In the model we studied, the fluid is Newtonian for small packing fractions, but develops a yield stress as the packing fraction increases, similar to several previous works [65,[69][70][71][72], as seen in Figure 2a-c. One can see the rise of solid-like properties in those fluidic systems.…”
Section: Shear Thickening Due To Functional Particle Infusionsupporting
confidence: 80%
“…Discretisation in space is realised by the discontinuous Galerkin (dG) method [ 68 , 69 , 70 ]. Domain is discretised by a quadrilateral mesh with a meshsize h .…”
Section: Hybrid Multiscale Methodsmentioning
confidence: 99%
“…These small differences might be attributed to the neglect of forces arising from the thermostat in the stress calculation or an effect observed in Ref. [48], where it was shown that the specific coupling of shear to thermostats may introduce small discrepancies in the calculation of viscosity. In Figure 1b we investigate the dependence of viscosity on shear rate as a function of stiffness for a polymer melt with chain length N = 15.…”
Section: Shear-thinning In Polymer Melts -A Molecular Analysismentioning
confidence: 99%